Review on Key Factors of Wireless Power Transfer Technology for Electric Vehicles - Mya Eaindra Thein; Amornrat Kaewpradap (Engineering Journal, 2022)
Electric vehicles (EVs) have become an alternative option for a clean energy society. A new charging technology which is wireless charging has been developed to satisfy the limitations of EVs which are the electric drive range and battery storage. Companies like Tesla, BMW, and Nissan have already started to develop wireless charging for EVs. This paper presents a literature review on wireless charging of EVs. The existing technologies for Wireless Power Transfer (WPT) system are summarized for different power applications. Coil design plays the most vital role in the WPT system so the different coil design with the transferred efficiency is reviewed. The other important parameters and technical components like significant factors of WPT system, track layout of dynamic wireless charging, foreign object detection method, and position alignment method that are affecting the efficiency of the wireless charging system are also discussed. Lastly, health and safety concerns for human beings and living things are investigated.
Keywords: Wireless Power Transfer Systems; Internet of Things and Social Network Interactions